2018
DOI: 10.17722/ijme.v11i2.478
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leverage and Liquidity at Profitability with Investment Opportunity Set (IOS) as Intervening Variable- A Case study at manufacturing companies listed in Indonesian Stock Exchange in period 2013-2016

Abstract: The research aimed at knowing the influence of leverage and liquidity toward profitability with IOS as the intervening variable. The research samples were 71 companies listed in Indonesian Stock Exchange in period 2013-2016. Hypotheses testing by using structural equation model (SEM). Analysis results found th at: Liquidity did not influence toward IOS. Leverage did not influence to the profitability. IOS influences positively toward profitability. Leverage influence positively toward IOS. Liquidity influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…The number (-0.019755) shows that if the CR indicator increases by 1 unit while the other independent variables are fixed, then investment (IOS) will decrease by 0.019755. This research is in line with that conducted by Yendrawati & Adhianza (2013), Mun'im (2018 which states that CR has no effect on investment (IOS) but on the other hand Based on the results of multiple linear regression analysis in Figure 4.9, DER has a probability value of 0.0190, this value is below the significance level (0.05), so it can be concluded that the DER indicator has a significant effect on investment (IOS). The coefficient on the DER indicator shows the value (0.084088).…”
Section: Effect Current Ratio (Cr) On Investment Decisions In Mining ...supporting
confidence: 90%
“…The number (-0.019755) shows that if the CR indicator increases by 1 unit while the other independent variables are fixed, then investment (IOS) will decrease by 0.019755. This research is in line with that conducted by Yendrawati & Adhianza (2013), Mun'im (2018 which states that CR has no effect on investment (IOS) but on the other hand Based on the results of multiple linear regression analysis in Figure 4.9, DER has a probability value of 0.0190, this value is below the significance level (0.05), so it can be concluded that the DER indicator has a significant effect on investment (IOS). The coefficient on the DER indicator shows the value (0.084088).…”
Section: Effect Current Ratio (Cr) On Investment Decisions In Mining ...supporting
confidence: 90%
“…Leverage diukur menggunakan rasio utang pada modal (Debt to Equity) yang merupakan pengukuran seberapa jauh perusahaan dibiayai oleh hutang. Bagi sebagian investor rasio DER atau leverage tersebut bisa menjadi indikasi sejauh mana manajemen agresif dalam meningkatkan investasi agar menghasilkan keuntungan (Mun'im & Mauludin, 2018).…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnya yang mengkaji sejauhmana corporate governance, leverage dan profitabilitas menunjukkan variasi temuan, baik dari signifikansi maupun arah hubungannya (Hediono & Prasetyaningsih, 2019;Ifada & Inayah, 2017;Mun'im & Mauludin, 2018). Inkonsistensi hasil penelitian ini membuka ruang bagi penelitian ini untuk melakukan konfirmasi ulang bagaimanakah pola hubungan dan pengaruh corporate governance, leverage dan profitabilitas pada unit analisis yang berbeda.…”
Section: Pendahuluanunclassified